THE PROBLEM OF DISPARITY IN PAY BETWEEN WOMEN AND MEN FOR WORK OF THE SAME VALUE - Todorović, Marina (Political Review, 2025)
The starting point of this research is based on several complementary theoretical approaches, which allow for a comprehensive understanding of the phenomenon of the gender pay gap. Primarily, the work relies on the theory of historical institutionalism, in which the works of authors such as Douglass North, an American economist, and the American sociologist and political scientist, Theda Skocpol, are significant. This approach highlights that the outcomes of public policies are influenced not only by formal legal provisions and laws but also by so-called "non-policy" factors — networks of informal rules, habits, cultural patterns, and behaviors rooted in social and political reality. Thus, even when progressive public policies are formally adopted, their implementation may be limited by institutional inertia and resistance in practice. Additionally, insights from labor market segmentation theory will be applied, particularly the analyses of intellectuals such as Barbara Reskin, a sociologist, and Heidi Hartmann, an economist, who emphasize the existence of horizontal and vertical segregation of women in the employment sector, meaning their concentration in lower-paid sectors and underrepresentation in decision-making positions and top management. The research also builds upon findings from Joan Acker, a sociologist, who pointed to the existence of „gendered institutions“ and structures, such as the labor market, where gender hierarchies are socially constructed and reproduced. Through this perspective, the gender pay gap is not seen merely as a result of individual choices or qualifications but rather as a reflection of traditionally entrenched institutional and social patterns that produce and sustain gender inequality. The study also incorporates insights from economist Claudia Goldin, who, through the lens of historical institutionalism and labor market segmentation, emphasizes long-term structural “matrices of inequality” between women and men in the labor market. The main research question this paper seeks to address is: How do the socio-cultural norms influence the effectiveness of implementing policies aimed at reducing the gender pay gap? Methodologically, the research is based on scientific methods of content and discourse analysis, historical method, as well as induction and deduction. The analysis of data on gender wage differences in the Republic of Serbia draws from the 2023 survey by the Statistical Office of the Republic of Serbia, showing a reduction of the gender pay gap to 8.8%. However, a deeper analysis that includes factors such as education level, type of employment, and (un)employment rates among women reveals significantly greater disparities. Women are more often represented in lower-paid occupations, receive lower pensions (on average, 17% less), and experience higher unemployment rates, despite being more highly educated overall. Despite the adoption of the „Law on Gender Equality“ in 2021 and the „Action Plan for 2022–2023 as part of the Gender Equality Strategy for the period 2021–2030“, the labor market position of women has not seen significant improvement. Thorough considerations suggest that, despite certain normative progress achieved in recent years, the primary objective should be to ensure that public policies in the field of gender equality move beyond official declarations and formal regulations, and instead become effective mechanisms that not only monitor the outcomes of improved public policies but also strengthen the capacities of women for professional advancement. Particular emphasis should be placed on promoting women’s leadership and ensuring equal representation in decision-making processes, as sustainable economic equality cannot be achieved without these measures. It is equally important to recognize that the goal of such policies is not to neglect or marginalize men, but to establish a system where achievements, knowledge, and engagement of every individual are evaluated on equal grounds. Only policies that foster and acknowledge the potential of women across all professional sectors can be regarded as truly effective and capable of driving broader social transformation.